Prescription Frequency and Predictors for the Use of Novel Direct Oral Anticoagulants for Secondary Stroke Prevention in the First Year after Their Marketing in Europe – A Multicentric Evaluation. Issue 5 (July 2014) - Luger, Sebastian; Hohmann, Carina; Kraft, Peter; Halmer, Ramona; Gunreben, Ignaz; Neumann-Haefelin, Tobias; Kleinschnitz, Christoph; Walter, Silke; Haripyan, Veronika; Steinmetz, Helmuth; Foerch, Christian; Pfeilschifter, Waltraud
Background: Direct oral anticoagulants (DOAC) are alternatives to the use of vitamin K antagonists (VKA) as oral anticoagulant therapies to prevent stroke in patients with atrial fibrillation. Aims: We assembled a representative secondary prevention cohort from four tertiary care stroke centers to identify factors that independently influence therapeutic decision making 1) not to anticoagulate with either VKA or DOAC and 2) to use DOAC if the patient appears suitable for oral anticoagulant therapy. Methods: We identified all patients discharged with the diagnoses 'ischemic stroke' (ICD-10 code 163) or 'transient ischemic attack' (G45) in combination with 'atrial fibrillation' (148) during 1 year. We performed binary logistic regression analyses to identify factors independently influencing the aforementioned decisions. Results: Our cohort comprised 758 patients. At discharge from the stroke service, 374 patients (49·3%) received oral anticoagulant therapy. Older age, severe stroke, poor recovery in the acute phase, and higher serum creatinine were independent factors to withhold oral anticoagulant therapy, whereas prior oral anticoagulant therapy favored the decision to anticoagulate. Among patients who were anticoagulated, prescription was balanced for VKA (50·3%) and DOAC (49·7%). Renal function and prior oral anticoagulant therapies were the most important factors in this decision. Conclusions: Shortly after their marketing, DOAC are used as frequently as VKA for secondary stroke prevention in patients with atrial fibrillation. The decision between VKA and DOAC is mainly determined by the patient's renal function and the absence or presence of prior oral anticoagulant therapy.